Portrait of Eugene Garfield - Bachrach, Louis Fabian
Black and white photograph of Eugene Garfield (1925-2017), a prominent American information scientist and pioneer in the field of scientometrics. He was the founder of the Institute for Scientific Information (ISI), a renowned academic publishing service that offered scientometric and bibliographic database services and specialized in citation index and analysis. Garfield was also the inventor of the Science Citation Index (SCI), Social Sciences Citation Index (SSCI), Current Contents, and Arts and Humanities Citation Index. These inventions provided an objective and quantitative basis for analyzing information flow in scientific communication and fostered the growth of the field of scientometrics.
Keywords: Garfield, Eugene; Information science; Information storage and retrieval systems; Citation indexes; Science publishing; Science--Information services; Institute for Scientific Information